Critical Bellman-Harris branching processes with infinite variance allowing state-dependent immigration - Mitov, Kosto V.; Yanev, Nickolay M. (Stochastic models, 2002)
The branching processes with state-dependent immigration are considered as alternating regenerative processes. The main purpose is to demonstrate some new "regenerative" methods. Critical Bellman-Harris branching processes with state-dependent immigration are investigated and new limit theorems are obtained in the case of an infinite offspring variance and possibly infinite mean of the immigrants.